(untitled) - Hubbard, R Glenn (Reading, Massachusetts, 1997)
The book is organized into six parts. Part I: Introduction, includes the reasons for using an economic approach to studying money, financial markets and institutions, and the economy; the role of money within the financial system; and an overview of the role played by different elements of the financial system in matching savers and borrowers and providing risk-sharing, liquidity, and information services. Part II, Interest rates, focuses on how interest rates are determined. Part III, Financial markets, extends the analysis to encompass financial markets more broadly. Part IV, Financial institutions, continues to use the concepts of risk sharing, liquidity, and information to explain why and how financial institutions and instruments evolve. Part V, The money suply process and monetary policy, opens the discussion of the links between the financial system and macroeconomy. Part VI, The financial system and the macroeconomy, studies the impact of monetary policy on the macroeconomy
Keywords: Banks and banking,Finance,International finance,Money